How Social Media Algorithms Potentially Reinforce Radical Views - Kuncoro, Hestutomo Restu; Hasanah, Khuswatun (Insignia: Journal of International Relations, 2024)
This research delves into the complexities of social media's role as a platform for communication, examining how it facilitates the spread of radical ideologies while simultaneously serving as a space for deradicalization. Through a comprehensive literature review, the researchers aim to combine existing findings with fresh insights employong qualitative analyses. Central to the study is the application of the Uses and Gratifications Theory (UGT), which posits that users actively select content based on specific needs and desires. By applying UGT, the research seeks to uncover the underlying motivations driving users to engage with extremist content on social media, offering a nuanced perspective on the platform's societal influence and potential implications for policy and platform modifications. The study employing comprehensive literature reviewmethodology, the research collects and analyzes a wide range of scholarly articles, reports, and relevant sources to provide a comprehensive overview of how social media contributes to the disemination of radical views. Based on the findings, Social media platforms, through their algorithm-driven content curation and interactive community structures, create environments where radical ideologies are normalized and amplified within echo chambers, subtly increasing the likelihood of real-world radicalization. Media consumers, guided by the Uses and Gratifications Theory (UGT), actively shape their content experiences on platforms like X, Facebook, and Youtube. However, the platforms’designs and algorithms can inadvertently drive radicalization. Countermeasures, informed by understanding users' motivations via UGT, are crucial to mitigate this, but they must be regularly evaluated for effectiveness. Keywords: dissemination, radical views, social media, UGT